Litiasis vesicular en paciente de 21 años con embarazo de 14 semanas - Rodriguez Ramirez, Viviana Maria (2018)
Cholelithiasis is one of the 32 most frequent diseases associated with pregnancy, which manifests itself in the 2nd or 3rd trimester. Its complications, from acute cholecystitis to peritonitis or pancreatitis, are conditions that can lead to death for both the mother and the fetus. Biliary lithiasis rates of 0.5 to 1.6 have been found for every 1,000 pregnant women. The bile that forms the stones is supersaturated with cholesterol or bilirubin. It is divided into two types of lithiasis: 80% of compound cholesterol and 20% of black or brown pigmentation composed of the sales of calcium with bilirubin. The most frequent risk factors that originate in the formation of gallstones are : age, female sex, obesity, hyperlipidemia, pregnancy, multiparity and drugs (such as the group of fibrates, ceftriaxone or contraceptives), participate in the lithogenesis. Abdominal ultrasound, visualization of the presence in the gallbladder, in addition to liver function tests (got, gpt, bilirubins and alkaline phosphatase). The 21-year-old patient from the city of Babahoyo seldom visits the maternal hospital due to several episodes of nausea and vomiting, is admitted for rest, remains with permeable peripheral access, medication is administered and in stable condition with a single 14-week pregnancy , through an ultrasound study was diagnosis with vesicular lithiasis. The initial treatment of cholelithiasis during pregnancy consists of digestive rest, eliminating foods with high fat content, intravenous fluids, correction of electrolyte imbalance and analgesic